Mind wandering: Tracking perceptual decoupling, mental improvisation, and mental navigation - Gonçalves, Óscar F. (2020)
Background: Mind wandering is a prevalent phenomenon. However, the concept of mind wandering is associated with distinct and often orthogonal concepts, and researchers are still debating the best strategies to gain access to mind-wandering processes. Nonetheless, there is a progressive acknowledgment that mind wandering is a multidimensional and heterogeneous construct. We argue that to fully understand mind wandering, we need to look at dimensions assessing the process (i.e., perceptual decoupling), dynamics (i.e., mental improvisation), and content (i.e., mental navigation). Objective: The objective of this study was to develop a self-report measure of mind wandering—the Mind Wandering Inventory (MWI)—to capture the heterogeneity of mind wandering in terms of process, dynamic, and content components. Method: Five language versions of the MWI were administered to an international sample of 1,162 individuals. Results: Results showed that the MWI had good levels of internal consistency. In terms of internal structure, we found a first factor to index perceptual decoupling, a second to index mental improvisation, and a third to index mental navigation. Additionally, a study of concurrent validity with Spontaneous and Deliberate Mind Wandering scales suggested that MWI has significant correlations with previous mind-wandering scales and that factors 1 (perceptual decoupling) and 2 (mental improvisation) seemed to be more closely associated with spontaneous than deliberate mind wandering. Finally, individuals coming from sciences major background reported increased levels of mind wandering when compared with participants from both health, social and human sciences background.